The antioxidant, anti-inflammatory, and anti-apoptotic effects of sesamin against cisplatin-induced renal and testicular toxicity in rats - Ahmed E. Altyar; Ghadeer M. Albadrani; Sameh M. Farouk; Mariam K. Alamoudi; Amany A. Sayed; Zuhair M. Mohammedsaleh; Muath Q. Al-Ghadi; Rasha Mohammed Saleem; Hader I. Sakr; Mohamed M. Abdel-Daim (Renal Failure)
Purpose The present study investigated the nephron-testicular protective effects of sesamin against cisplatin (CP)-induced acute renal and testicular injuries.Methods Thirty-two male Wistar rats were allocated to receive carboxymethylcellulose (0.5%, as sesamin vehicle), CP (a single i.p. 5 mg/kg dose), CP plus sesamin at 10 or 20 mg/kg orally for 10 days.Results Data analysis showed significant increases in serum urea, creatinine, interleukin (IL)-1, IL-6, and tumor necrosis factor-α (TNF-α), as well as renal and testicular tissue malondialdehyde and nitric-oxide concentrations in CP-intoxicated rats in comparison to control animals. On the contrary, rats treated with CP only exhibited significantly lower (p < .05) serum testosterone, tissue glutathione, and activities of endogenous antioxidant enzymes compared to control rats. Histopathologically examining CP-intoxicated rats’ tissues using H&E and PAS stains showed atrophied glomeruli, interstitial inflammatory cells, atypic tubular epithelium with focal apoptosis, and reduced mucopolysaccharide content. Further, immunohistochemical staining of the same group revealed an increase in p53 and cyclooxygenase-II (Cox-II) expression in renal and testicular tissues. Treatment with sesamin alleviated almost all the changes mentioned above in a dose-dependent manner, with the 20 mg/kg dose restoring several parameters’ concentrations to normal ranges.Conclusions In brief, sesamin could protect the kidneys and testes against CP toxicity through its antioxidant, anti-inflammatory, and anti-apoptotic effects.